Hemiparesis Alterans: Laporan Kasus - Mutia Diah Pratiwi; Fidha Rahmayani (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2021)
ABSTRACT Background: Stroke is one of the most frequent cases with high morbidity and mortality. There are particular cases in which ipsilateral cranial nerve signs coexist with contralateral hemiparesis. Case Illustration: A 23-year-old woman experienced right-sided weakness, could not open her left eye, had double vision and slurred speech. Blood pressure measured was 130/100 mmHg on a physical examination. On neurological examination she had both ptosis and dilated pupil on her left eye, negative direct and consensual light reflex on her left eye, paralysis of the occulomotorius and trochlearis cranial nerve on the left, right facial weakness, and tongue deviation to the right on protrution. Tone muscle strength of the upper extremities was rated on a scale of 3/5 and 2/5 on the lower extremities with positive Babinski and Chaddok reflexes on the right side. On a chest x-ray cardiomegaly without pulmonary edema was seen and an ischemic lesion in internal capsule was found on a head CT scan without contrast. The patient was diagnosed with alternating hemiparesis and given 80-mg aspirin once a day. Discussion: Contralateral hemiparesis, ipsilateral occulomotorius nerve paresis, contralateral facialis and hypoglossal nerve paresis were clinically seen on patient. Imaging test result showed ischemic lesion, but further imaging test was needed to investigate brain stem involvement. Eighty milligrams of aspirin once a day was beneficial, yet clopidogrel with initial dose of 300mg and maintenance dose 75mg once a day could as well be prescribed. Conclusion: Superior alternating hemiparesis or Weber syndrome is likely to be the cause of death so immediate diagnosis and treatment are needed for patient diagnosed with alternating hemiparesis. The risk factors of alternating hemiparesis are multifactorial and need to be investigated